Family communication - Segrin, Chris (LEA's communication series., 2005)
This advanced text carefully examines state-of-the-art research and theories of family communication and family relationships. In addition to presenting cutting-edge research, authors Chris Segrin and Jeanne Flora focus on classic theories and research findings that have influenced and revolutionized the way scholars conceptualize family interaction. Showing that answers to many questions about family communication can be found in current scientific research, the book introduces readers to fundamental issues in the study of family communication; explores what is known about communication in di.